2015
DOI: 10.1007/s10526-015-9682-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Beauveria bassiana infection on the feeding performance and antioxidant defence of red palm weevil, Rhynchophorus ferrugineus

Abstract: The entomopathogenic fungal infection of target hosts depends on pathogen fitness and host defence mechanisms. Pathogen-host interactions in red palm weevil, Rhynchophorus ferrugineus larvae are poorly understood. In order to explore this interaction, 4th, 8th, and 12th instar red palm weevil larvae were immersed in conidial suspensions of four isolates of Beauveria bassiana. Significant differences in the virulence of the tested isolates were revealed by LT 50 values. Conidia of B8463, a highly virulent isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 33 publications
8
44
0
Order By: Relevance
“…The present study revealed that all isolates exhibited more than 96% conidial viability (F = 0.36; df = 2, 12; P = 0.708), even from the least virulent studied isolate 7234. These findings are in agreement with previous studies indicating that low virulence among highly viable isolates of fungi reflects that virulence is regulated by multiple sets of traits (Hussain et al 2015 andHussain et al 2016). In the present study, significant differences (F = 101; df = 2, 12; P < 0.0001) in Pr1 activity in all of the studied EPF isolates were also recorded.…”
Section: Pathogen Virulencesupporting
confidence: 93%
See 1 more Smart Citation
“…The present study revealed that all isolates exhibited more than 96% conidial viability (F = 0.36; df = 2, 12; P = 0.708), even from the least virulent studied isolate 7234. These findings are in agreement with previous studies indicating that low virulence among highly viable isolates of fungi reflects that virulence is regulated by multiple sets of traits (Hussain et al 2015 andHussain et al 2016). In the present study, significant differences (F = 101; df = 2, 12; P < 0.0001) in Pr1 activity in all of the studied EPF isolates were also recorded.…”
Section: Pathogen Virulencesupporting
confidence: 93%
“…The protease (Pr1) activity of the conidial suspensions of all tested isolates was assayed by recording the release of nitroanilide (NA) at 405 nm, using succinyl-Ala-Ala-Pro-Phe-p-nitroanilide substrate as described by Hussain et al (2015).…”
Section: Cuticle Degrading Protease Activitymentioning
confidence: 99%
“…These three populations were separately maintained on pineapples in perforated cages (57.5 × 29 × 58 cm) at 30±1°C. Second-instar grubs were carefully shifted to an artificial diet (consisting of 45 g/L wheat flour, 45 g/L corn flour, 45 g/L yeast, 1.6 g/L sorbic acid, 4 g/L ascorbic acid, two capsules of pharmaton per litre, 500 mg/L tetracycline, and 17.5 g/L agar in 1000 mL of distilled H2O) in perforated, transparent plastic cups with a capacity of 400 mL (Hussain et al, 2015). Larvae from each regional population were reared separately at 30 ± 1°C with 75% ± 5% relative humidity in an incubator (Sanyo).…”
Section: Maintenance Of Red Palm Weevilsmentioning
confidence: 99%
“…The whole study was repeated over time. The insect, diet and frass weights were used to determine the feeding performance by calculating the efficacy of conversion of ingested food [ECI = 100 × dry weight gained by the larva/dry weight of food consumed] and the efficacy of conversion of digested food [ECD = weight gained by the larva/(food ingested -dry weight of frass)] (Hussain et al, 2009;Hussain et al, 2015). The data on the growth indices were analysed by one-way ANOVA.…”
Section: Impact Of Insecticides On the Growth And Development Of R Fmentioning
confidence: 99%
“…Fungal entomopathogens which are natural suppressors of insects are often chosen as microbial control agents of polyphagous insect pests [13] and are considered valuable control agents of Coleoptera [11,13,14,15,16,17,18,19]. Four entomopathogenic fungi, Metarhizium anisopliae (Metschnikoff) Sorokin (Hypocreales: Clavicipitaceae), Beauveria bassiana (Balsamo) Vuillemin (Hypocreales: Clavicipitaceae), Purpureocillium lilacinum (Thom) Luangsa-Ard, Houbraken, Hywel-Jones and Samson [20] (= Paecilomyces lilacinus ) (Hypocreales: Ophiocordycipitaceae) and Aspergillus ochraceous Wilhelm (Eurotiales: Trichocomaceae) were isolated from DRW larvae in a survey conducted monthly from June 1979 through December 1980 in nine citrus groves and one ornamental nursery in central Florida [15].…”
Section: Introductionmentioning
confidence: 99%